Zombies, Truants, and Flash Mobs: How Youth Organizers Respond to and Shape Youth Policy. Issue 13 (April 2015) - Conner, Jerusha O.; Rosen, Sonia M.
Youth organizing groups combine strategies from the fields of youth development and community organizing in order to mobilize young people to take collective action. Significantly, organizing work acknowledges that youth are commonly blamed for social problems that are beyond their control and repositions these youth as agents of positive social change. This approach complicates policy scholarship, which understands stakeholders as "targets" of policy initiatives. In a seminal work on public policy, Schneider and Ingram identify four quadrants in which target populations can be placed by policy formulations: advantaged (those with high power and a positive valence), contenders (those with high power and a negative valence), dependents (those with low power and a positive valence) and deviants (those with low power and a negative valence). Schneider and Ingram point out that young people are generally positioned as "dependents." However, this chapter draws on empirical data from one youth organizing group to demonstrate how youth assert themselves as powerful stakeholders in important decision-making processes, contradicting policymakers' construction of them as passive and weak.